Penyuluhan Dan Pendampingan Konsep Hidup Sehat Ala Rosulullah Di Pondok Pesantren Darussalam - Abdurrohman; Miksan Ansori (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
Health is one of the indicators to measure the level of santri's well-being. The degree of health of Santri is influenced by 4 main factors, namely environmental factors, behavior, health services, and heredity. The biggest and most affecting factors in health are environmental factors. Environmental health efforts as a form of preventive activities are aimed at realizing the quality of a healthy environment, both physical, chemical, biological, and social that allows each individual or Santri to achieve the highest degree of health (Law No. 36 of 2009 on Health). The extension and mentoring strategy is the initial process to prepare researchers to Santri so that the counseling and mentoring process can be carried out in a planned, programmatic, and carried out with Santri / community. In this case, researchers also apply the arrangement of extension and mentoring strategies using the PAR method; first Know the real condition of Santri / community (to know), second Understand community problems (to understand), third Plan community problem solving (to plan), fourth Take action (to action), fifth Reflection (to reflection)The training was followed by darrussalam's son santri, namely by providing education about healthy living a la rosulullah such as an example of cleaning yourself with enough and holy water, bewak / toothbrush, get up early, eat enough, eat slowly, do not drink water in one breath, fasting, eating dates, and exercising. This program can be successful because there is good cooperation between researchers and the administrators of the cottage and santri, and I am very grateful to the students who have studied together with me and also received me well this institution, namely darussalam pesantren hut sumbersari kencong siege siege kediri, for the spirit of the students then this program can run well and also have a good impact for the students in the boarding school Darussalam sumbersari kencong kepung besiege Kediri.